Mengintegrasikan Kecerdasan Emosional, Kecerdasan Spiritual Dan Kecerdasan Buatan Dalam Praktik-Praktik Manajemen Sumber Daya Manusia Pada Organisasi Bisnis - Hermanto, Muhammad (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2024)
The increasing complexity and dynamism of the business world make the integration of Emotional Intelligence (EQ), Spiritual Intelligence (SQ), and Artificial Intelligence (AI) in Human Resource Management (HRM) practices a holistic approach to enhancing workplace effectiveness and well-being. Emotional Intelligence plays a crucial role in managing interpersonal relationships, communication, and conflict management, which are vital for effective leadership and teamwork. Spiritual Intelligence supports the search for meaning and purpose in work, fostering an organizational culture aligned with personal and collective values. On the other hand, Artificial Intelligence automates processes, provides data-driven analytics, and improves operational efficiency through advanced technology. Integrating these three forms of intelligence can create a more productive, innovative, and fulfilling work environment. This article reviews the fundamental theories of each type of intelligence and explains how their application in HRM practices can yield significant benefits for organizations.